A new species of Alhajarmyia Stuckenberg (Diptera: Vermileonidae), the first wormlion fly described from East Africa and its biogeographical implications - Swart, Vaughn R.; Kirk-Spriggs, Ashley H.; Copeland, Robert S. (Zootaxa, 2015)
A second species of the genus Alhajarmyia Stuckenberg (A. stuckenbergi Swart, Kirk-Spriggs & Copeland, sp. n.), is described and figured, from the Eastern Arc Mountains of Kenya (Kasigau Mountain and Taita Hills), being the first vermileonid recorded from East Africa. The species is shown to differ from its congener, A. umbraticola (Stuckenberg & Fisher), described from Oman in the Arabian Peninsula, based on external characters including male and female terminalia. An identification key is provided together with distribution maps for the two species, and biogeographical aspects are discussed.